The Aerodynamic Characteristics of a Diamond Joined-Wing Morphing Aircraft - Shuai Miao; Xiaoyong Ma; Cheng Chen; Binhua He; Yong Huang (International Journal of Aerospace Engineering)
This paper presents a new-concept aircraft with a diamond joined-wing morphing configuration, which simultaneously adjusts the sweep angles of both the front wing and rear wings by a telescopic support rod. The compressible Navier-Stokes equations in the conservative form are solved to analyze the configuration characteristics and the aerodynamic benefits of this aircraft with different values of sweep angle (15°, 60°) and Mach number. The maximum lift-to-drag ratio is about 13.5 at M=0.5 and α=4°, 12.8 at M=0.75 and α=4°, and 3.4 at M=1.5 and α=6°, respectively. Compared with traditional morphing aircraft, the main advantages of this configuration include better transonic and supersonic performance, better lift characteristics in the state of a high-aspect ratio, and lower zero-lift drag in the supersonic state. The lift ratio of the front and rear wings shows a good similarity at different Mach numbers, especially for the 15° model, and the value eventually tends to be 1.3 at α=12°. Meanwhile, the flow field characteristics and interference characteristics of the front and rear wings are studied. The increase in the angle of attack, incoming flow velocity, and distance between the front and rear wings can reduce the interference between front and rear wings. The influence from upstream components is proven to improve the aerodynamic characteristics of the rear wing, especially at α=8°.